Aktualisasi Nilai-nilai ‘Puputan’ dalam Pembangunan Karakter Bangsa - I Gde Parimartha (Jurnal Kajian Bali (Journal of Bali Studies), 2011)
AbstractThis article seeks to analyze the actualisation of the values and spiritof puputan (war until the end) by connecting it to current attempts of nationand charater building in Indonesia. It examines the values of puputan inits social and historical context and relates them to contemporary issuesin Indonesia. The topic of character building gains high currency inthe backdrop of moral degradation marked by cases of corruption,destruction, and violence. Bali has inherited the spirit of puputan fromthe struggle against Dutch colonialism; it is therefore a challenging taskto examine how far this set of values can contribute to the developmentof national character. The article argues that values inherent in the spiritof puputan, such as loyalty, honesty, bravery, trust, and optimism, arerelevant to the current attempts at national character building.